Anaerobic Contribution Determined in Swimming Distances: Relation with Performance - Campos, Eduardo Z.; Kalva-Filho, Carlos A.; Gobbi, Ronaldo B.; Barbieri, Ricardo A.; Almeida, Nayara P.; Papoti, Marcelo (Frontiers in Physiology, 2017)
Total anaerobic contribution (TAn) con be assessed by accumulated oxygen deficit, and through sum of glycolytic and phosphagen contribution which enable the evaluation of TAn without influences on mechanical parameters. However, little is known about the difference of TAn within swimming distances. Therefore, the objective of the present study was to determine and compare the TAn in different performances using the backward extrapolation technique and amount of lactate accumulated during exercise, and relate it with swimming performance. Fourteen competitive swimmers performed five maximal front crawl swims of 50, 100, 200, 400, and 800 m. The total phosphagen (AnAl) and glycolytic (AnLa) contributions were assumed as the fast component of post-exercise oxygen consumption (EPOCFAST) and amount of blood lactate accumulated during exercise, respectively. TAn was the sum of AnAl and AnLa. Significantly lower values of AnLa were observed in the 800 m (p < 0.01) than other distances. For AnAl, the 50 m performance presented the lowest values, followed by 100 and 800 m (p < 0.01). The highest values of AnAl were observed in the 200 and 400 m (p > 0.13). The TAn was significantly higher in the 200 and 400 m performances than observed at 50 and 800 m (p < 0.01). Anaerobic contributions were correlated with 50, 100, 200, and 400 m performances (p < 0.01). The AnAl contribution was not correlated with 400m performance. Anaerobic parameters were not correlated with 800 m performance. In conclusion, the highest values of anaerobic contribution were observed in the 200 and 400 m distances. Moreover, TAn is important to performances below 400 m, and may be used in training routines.